"Alcohol is Humanity's enemy!" Propaganda Posters and the 1922 Swedish Prohibition Referendum. (15th March 2023) - O'Hagan, Lauren Alex
ABSTRACT: In the early twentieth century, intense public debate was taking place in Sweden around the control of alcohol consumption. Under intense pressure from the growing temperance movement, the Swedish government passed a motion to hold a referendum on 27 August 1922 to determine whether a total prohibition of alcohol should be implemented. One of the most important means of influencing public opinions was the propaganda poster, which relied on simple pictures, catchy slogans and bright colours to domesticate the prohibition debate and make it easily digestible. This paper conducts a study of the posters produced by the 'yes' and 'no' campaigns during the lead-up to the referendum. It finds that, despite their opposing arguments, both sides used similar arguments based around the breakdown of family life and the breakdown of Swedish society, depicting an imagined present or future in which Sweden was lawless and traditional values were threatened. Furthermore, both sides stirred up class warfare, creating conflict between the Swedish people and the government, and depicting alcoholism as a predominantly male, working-class problem. Overall, it argues that the 'no' campaign posters were ultimately more successful because of their ability to play on voters' emotions rather than use rational arguments.